EMERGENCY MEDICINE FELLOWSHIP: LENGTH-OF-STAY IMPACT OF ESTABLISHING A LARGE POST-RESIDENCY TRAINING PROGRAM - Bashir, Khalid; Kodumayil, Ashid; Farook, Saleem; Pathan, Sameer; Kumar, Thirmoorthy samy; AlKahl, Abdllatif; Jenkins, Dominic; Thomas, Stephen (Journal of Ayub Medical College Abbottabad, 2020)
Background: The length of stay (LOS) is an important operational parameter closely followed in emergency department (ED). This study aims to assess operations impacts of a large post-residency EM Fellowship (EMF) program on LOS. Methods: This was a retrospective database analysis of data collected automatically by the study ED’s electronic medical record (EMR) for one full academic year, starting in September 2016. The main dependent variable was LOSfor the cases discharged after EM-only evaluation (LOSDCEM), and the independent variable of interest was the proportion of EMFs as a % of all on-duty ED physicians during the shift the patient presented. Results: During the study period, the ED census for patients discharged after EM-only evaluation was 327,527. Exclusion of 5,803 EMR-downtime cases (1.8% of 327,527) and 845 (0.3% of 327,527) cases with LOS exceeding 24 hours, the final study set comprised 320,879 LOSDCEM cases. The EMF proportion of on-duty ED physicians, was statistically significant at the lowest three Ï„ levels but not significant at the higher six Ï„ levels. For the 10th, 20th, and 30th percentiles of LOSDCEM, the % relative improvements in LOSDCEM achieved by increasing the EMF proportion 1% were, respectively, 13% (6.5/52), 8% (6.8/83), and 7% (8.1/115). Conclusion: The LOSDCEM does not appear to be unfavourably impacted by increasing the proportion of EMFs as a % of all on-duty ED physicians. The EMFs numbers (as a percentage of all on-duty physicians) disproportionately improves LOSDCEM for those patients with shorter LOS. Keywords: Emergency department; Operation parameters: Length-of-stay; Trainees; EM fellowship; Emergency Medicine Fellowship